Pemecahan Masalah: Studi Terkait Peran Jenis Kelamin pada Model Mental Mahasiswa - Irawan, Wahyu Henky; Mulyani, Andini Endah Sri; Intsani, Nadila Choirunnisa’; A’fwandi, Akhmad Haidar (Universitas Islam Negeri Sayyid Ali Rahmatullah Tulungagung, 2024)
The purpose of this study is to describe the mental model of students in solving algebraic proof problems reviewed based on their gender. This study is a descriptive study. Data and data sources were obtained through problem-solving questionnaire instruments and subject interviews. The study was conducted at UIN Maulana Malik Ibrahim Malang. The subjects used were one male student and one female student with high GPAs. The validity of the data was tested using time triangulation. Data analysis refers to Miles Huberman's data analysis technique. The results of the study indicate that the mental model of male students in solving algebraic proof problems includes an implicational mental model and a functional mental model, while in terms of structure, the syllogistic decision making that occurs is invalid. While the mental model of female students in solving algebraic proof problems includes an implicational mental model, a functional mental model, and a structural mental model.